Recorrido comporta-específico : el espacio como especulación heterotópica (2017)
This project is the result of the inconformity felt around preconceptions regarding the design practice. Through several methods that unite art and design, this investigation unwrapped the possibility of opening a speculative door to the design practice. In order to achieve this, physical space became the metaphor that gradually stopped having physical traits and instead became the way to describe how creative processes should work.